Proceedings of the ACM International Conference on Interactive Experiences for TV and Online Video 2014
DOI: 10.1145/2602299.2602307
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cinematic cuts on human attention

Abstract: Understanding the factors that determine human attention in videos is important for many applications, such as user inter face design in interactive television (iTV), continuity editing, or data compression techniques. In this article, we identify the demands that cinematic cuts impose on human attention. We hypothesize, test, and confirm that after cuts the view ers' attention is quickly attracted by repeated visual content. We conclude with a recommendation for future models of vi sual attention in videos an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…The presence of pre-cut motion without the continuing post-cut motion may draw attention to the cut due to the sudden and unexpected termination of motion. Recent evidence from a novel side-by-side film-viewing paradigm provided evidence in support of such motion tracking as participants found it easier to saccade to cuts in which motion was continuous across a cut compared to cuts without continuity of motion (Valuch, Ansorge, Buchinger, Patrone, & Scherzer, 2014). Our analysis of gaze mobility also indicated that -Post cuts that were detected had higher gaze velocity than the same cuts that were missed.…”
Section: Discussionsupporting
confidence: 55%
“…The presence of pre-cut motion without the continuing post-cut motion may draw attention to the cut due to the sudden and unexpected termination of motion. Recent evidence from a novel side-by-side film-viewing paradigm provided evidence in support of such motion tracking as participants found it easier to saccade to cuts in which motion was continuous across a cut compared to cuts without continuity of motion (Valuch, Ansorge, Buchinger, Patrone, & Scherzer, 2014). Our analysis of gaze mobility also indicated that -Post cuts that were detected had higher gaze velocity than the same cuts that were missed.…”
Section: Discussionsupporting
confidence: 55%
“…-Scene switches -for example an indoor scene changing to outdoor may catch the users attention and take it from the tablet to the TV. This phenomena is discussed in more detail by Valuch et al [79].…”
Section: Concentrationmentioning
confidence: 84%
“…Further, Neate et al [34] have looked at how to effectively shift a user's attention between screens in a crossdevice experience, and how one may vary visual complexity on a handheld device to compensate for the perceived complexity on the TV material [33]. Finally, Valuch et al [43], when considering the effect of cinematic cuts on a single screen, noted that viewers were able to better re-orient their attention more quickly if visual content is repeated from a pre-cut scene, suggesting that a similar approach may aid reorientation of visual attention in a cross-device experience.…”
Section: Dual-screen Attention: Hinderances and Enhancementsmentioning
confidence: 99%